The Many Perceptions of Reality in Search of the Self: Reading Yangsze Choo’s The Ghost Bride - Dalal, Sanghamitra (SARE: Southeast Asian Review of English, 2020)
In this article I will read Yangsze Choo’s speculative fiction novel The Ghost Bride (2013), which not only refers to the ancient Chinese tradition of “ghost-marriage” or “spirit-weddings” but also traverses the phantasmic world of the Chinese afterlife and an imaginary land conceived as the “Plains of the Dead”. I will examine how Choo effectively utilizes Chinese myths and folklore in order to construct the parallel worlds of the living and the dead. I will particularly focus on the fictional character, the mysterious guardian spirit, Er Lang, who evokes the myth of Er Lang Shen, the great Chinese warrior God of Heaven who possesses an esoteric Third-Eye of Enlightenment on his forehead. In the course of my analysis, I will explore the problematics of the concept of reality in relation to the genre of speculative fiction, which stereotypically embodies elements of fantasy. However, I will argue, through my reading of The Ghost Bride, that human perceptions of reality should not be constrained by what can only be seen with mortal eyes, but what can also be discerned through the eyes of the inner mind.